Religion, migration, settlement : reflections on post-1990 immigration to Finland - Martikainen, Tuomas. (International Studies in Religion and Society, 2013)
In Religion, Migration, Settlement , Tuomas Martikainen provides an account of the impact of immigration on the field of religion in Finland since the 1990s. As a historical country of emigration that has turned into one of immigration, Finland provides an illuminating case study of the complexities of post-Cold War migration. The book analyses processes of migrant settlement from the viewpoint of religious organisations by applying theoretical perspectives to immigrant integration, global-local dynamics, governance of religious diversity, processes of migrant settlement and structural adaptation. The book is of relevance to those grappling with the impact of international migration on contemporary religious developments.